Fatores preditivos da qualidade de vida e da intensidade de sintomas do transtorno de déficit de atenção e hiperatividade em crianças e adolescentes - Lemes, Paula (2016)
Introduction: Attention Deficit Hyperactivity Disorder (ADHD) in children and adolescents is an important source of referral to the health system due to the multidimensional impairments in these individuals lives, especially in the academic, social and family contexts, with an impact on their quality of life (QoL). Thus, knowing the factors associated with the symptoms and damages caused by this clinical condition will allow a better understanding of the disorder, consequently the direction of the most effective therapeutic strategies. Therefore, this research aimed to verify if neuropsychological performance and school performance are predictive factors of the intensity of symptoms of inattention and hyperactivity and of the quality of life. Methods: A total of 96 children/adolescents aged 6 to 16 years (mean = 10.23 years; SD = 2.37) with a ADHD diagnosis participated in the study. We applied: SNAP-IV questionnaire to assess the symptoms intensity of inattention and hyperactivity; TDE to assess school performance; WISC-III to assess neuropsychological performance; and Peds-QL 4.0 to assess quality of life. Correlation analysis and the General Linear Model (GLM) were performed. Results: In the univariate analysis, sex had a significant effect on the symptoms intensity of inattention and hyperactivity and on the physical domain of QoL; age had an effect only on the symptoms intensity of inattention and on the social domain of QoL; the writing, arithmetic, reading and total scores of school performance had effects in the academic domain of QoL. In the multivariate analysis, neuropsychological performance showed effect on the symptoms intensity and on the social domain of QoL; school performance had effect on the physical, emotional and social domains of QoL. Conclusions: Neuropsychological performance dit not show to be a predictive factor of the symptoms intensity of inattention and hyperactivity and the quality of life of children and adolescents with ADHD. School performance was predictive of both symptoms intensity and quality of life in the group studied. The results of this study imply the need for greater attention of children and adolescents well-being diagnosed with ADHD related to academic performance.